2011
DOI: 10.1002/uog.8881
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Down syndrome screening performance using first‐trimester serum markers

Abstract: Objective To evaluate the modeled predictive value of three current screening markers (pregnancy-associated plasma protein-A (PAPP-A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 24 publications
(28 reference statements)
3
25
1
Order By: Relevance
“…The finding that in trisomy-21 pregnancies serum PLGF at 11–13 weeks’ gestation is reduced is compatible with the results of previous case-control studies [6,7,8,9]. In a few of our cases of trisomy-21 examined before 11 weeks, the levels of PLGF were also lower than in euploid pregnancies and the PLGF MoM in trisomic fetuses did not change significantly with gestational age between 8 and 13 weeks.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The finding that in trisomy-21 pregnancies serum PLGF at 11–13 weeks’ gestation is reduced is compatible with the results of previous case-control studies [6,7,8,9]. In a few of our cases of trisomy-21 examined before 11 weeks, the levels of PLGF were also lower than in euploid pregnancies and the PLGF MoM in trisomic fetuses did not change significantly with gestational age between 8 and 13 weeks.…”
Section: Discussionsupporting
confidence: 81%
“…Two recent studies reporting in trisomy-21 pregnancies at 8–10 weeks reported contradictory results. Koster et al [8], who examined 151 cases of trisomy-21 at 8–13 weeks, including 60 at 8–10 weeks, found that the median PLGF MoM was 0.8 and this did not change significantly with gestational age, whereas Cowans et al [9] reported that the median MoM in 37 affected cases was increased to 1.3. A possible explanation for the findings of Cowans et al [9] is that the concentration of PLGF increases with storage time, because their samples from the trisomy-21 pregnancies were stored for up to 9 years, whereas the controls were assayed within 1 year of collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total hCG (thCG), which is a screening marker for DS in the second trimester of pregnancy, is increased in maternal serum from first-trimester DS pregnancies (Hallahan et al, 2000). However, when these four markers were added to the current first-trimester combined test algorithm the DR increased by only 3% (table 2a) (Koster et al, 2010d). These studies show that the predictive power of maternal serum markers is not constant during the first trimester.…”
Section: Proteomics Techniques To Identify New Screening Markers For mentioning
confidence: 94%
“…In the first trimester, PlGF levels in trisomy 21 cases have been found to be both increased [9,10] and decreased [11,12,13] compared to euploid controls. In part, this may be down to the precise gestational age at sampling.…”
Section: Introductionmentioning
confidence: 99%